ANALISIS VISUAL GAYA MENGGAMBAR PADA KOMIK AKSI INDONESIA - Andini Setya Arianti (Universitas Komputer Indonesia, 2019)
Comics are one of popular storytelling media which combines images and text, and is read through spesific order. Far before it was known as â€œcomicâ€, Indonesia already has several forms of storytelling, such as Wayang Beber and relief on Borobudurâ€™s temple. This forms are later known as comics, which evolve through times in Indonesia. Indonesian comics received many influences from other countries. Indonesian comics received most influences from America and Japan. These influences are seen on its storytelling, and also, its drawing style. The comics being analyzed on this thesis are those with action genre, also known as â€œkomik silatâ€ in the past, because this genre is one of the most popular genre. There are two titles picked to be analyzed, one is â€œPandji Tengkorakâ€, which represents older generation comic, and â€œRaibarongâ€, which represent a more modern comic. To understand how indonesian comics grows throughout times and the factors behind its growth, this research uses qualitative analysis and descriptive-comparative along with study case as its approach. The result shows the differences between drawing style of the two comics, caused by the trends existing on their respective eras. Internal factors such us the authors personal preferences and media used to create the comics also further influences their drawing styles.